Association between Number of Siblings and Cardiovascular Risk Factors in Childhood and in Adulthood: The Cardiovascular Risk in Young Finns Study - Pihlman Jukka; Magnussen Costan G.; Rovio Suvi P.; Pahkala Katja; Jokinen Eero; Laitinen Tomi P.; Hutri-Kähönen Nina; Tossavainen Päivi; Taittonen Leena; Kähönen Mika; Viikari Jorma S.A.; Raitakari Olli T.; et al. (Mosby Inc., 2022)
Objective: To determine the association of number of siblings on cardiovascular risk factors in childhood and in adulthood.
Study design: In total, 3554 participants (51% female) from the Cardiovascular Risk in Young Finns Study with cardiovascular disease risk factor data at baseline 1980 (age 3-18 years) and 2491 participants with longitudinal risk factor data at the 2011 follow-up. Participants were categorized by number of siblings at baseline (0, 1, or more than 1). Risk factors (body mass index, physical activity, hypertension, dyslipidemia, and overweight, and metabolic syndrome) in childhood and in adulthood were used as outcomes. Analyses were adjusted for age and sex.
Results: In childhood, participants without siblings had higher body mass index (18.2 kg/m2, 95% CI 18.0-18.3) than those with 1 sibling (17.9 kg/m2, 95% CI 17.8-18.0) or more than 1 sibling (17.8 kg/m2, 95% CI 17.7-17.9). Childhood physical activity index was lower among participants without siblings (SD -0.08, 95% CI -0.16-0.00) compared with participants with 1 sibling (SD 0.06, 95%CI 0.01-0.11) or more than 1 sibling (SD -0.02, 95% CI -0.07-0.03). OR for adulthood hypertension was lower among participants with 1 sibling (OR 0.73, 95% CI 0.54-0.98) and more than 1 sibling (OR 0.71, 95% CI 0.52-0.97) compared with participants with no siblings. OR for obesity was lower among participants with 1 sibling (OR 0.72, 95% CI 0.54-0.95) and more than 1 sibling (OR 0.75, 95% CI 0.56-1.01) compared with those with no siblings.
Conclusions: Children without siblings had poorer cardiovascular risk factor levels in childhood and in adulthood. The number of siblings could help identify individuals at increased risk that might benefit from early intervention.